New York State Building (Pacific Novelty Co.)
On verso: New York with an appropriation of $750,000 erected the largest of the State buildings. It is four stories in height and has a frontage of 250 feet and 100 feet deep. On the ground floor there is a magnificent ballroom. A dining room is also a feature of the building, a complete cuisine being maintained. The ceiling of the dining room cost $15,000. There is also a suite of rooms for the Governor of New York.